Gender impacts of COVID-19 on the labor market and household wellbeing in Pakistan - Emcet O. Taş; Tanima Ahmed; Norihiko Matsuda; Shinsaku Nomura (Review of Economic Analysis (REA), 2022)
This study examines the gender impacts of the COVID-19 pandemic on the labor market and household wellbeing, using an online survey of the users of Pakistan's largest online job platform. The analysis shows that the pandemic led to an unprecedented level of economic insecurity for employees and employers alike, resulting in widespread job loss, business closures, a slowdown in business activity, and reduced working hours. The sectors where female workers are heavily concentrated, such as education, were more severely affected. The pandemic has also led to a disproportionate increase in women's unpaid care work and increased their reported rates of stress and anxiety. These findings suggest that the pandemic had significant wellbeing impacts on women in Pakistan, including a decline in the female labor force participation rate, which is already among the world's lowest.
Keywords: J22; J23; I30; 330; COVID-19; labor market; income; unpaid work; Pakistan